Inventory Control System Using Waterfall Development Model - Talmizie Amron, Mohd; binti Abu Hassan, Shabirah; Shukri Saleh Hudin, Mohamad; Janom, Norjansalika (International Journal of Engineering and Technology, 2018)
Information system innovation progress is turning out to be speedier and simpler to use. In many cases, there are an organization that still utilize the customary route in preparing their information.Â  Customary routes will require people to move from one place to another to achieve their goals. In the case of Finance Department, UiTM Kampus Kuala Terengganu, the manual process involving the staffs to fulfill and submit the form and officer will approval and validation. The storekeeper will verify the availability of the item in the store. Using manual processes consumes a lot of time, high risk of human error and involves a lot of papers as well as files. Therefore, Bendahari Inventory Control System (BICS) was proposed to help the Finance Department to be more systematic in handling the inventory control. The implementation of the Waterfall Model in this research was turned to be useful and appropriate to help building up the system.Â Â